Longitudinal Protection Scheme of HVDC Line Based On the Characteristics of Branch Current. Issue 3 (February 2020) - Xu, Zhiming; Liu, Jun; Bai, Tianyu; Tang, Wenqiao
Abstract: For the traditional high-voltage direct current (HVDC) lines with poor protection rapidity and low resistance to high resistance, This paper puts forward a kind of based on HVDC line reactance flat wave branch current changes of the longitudinal protection scheme. This scheme takes advantage of the fact that the specific harmonic component of the flat-wave reactance branch current is short-circuited by the equivalent dc filter bank when it is internal fault. The characteristics of no such harmonic component flow on the branch can be used as the basis to identify internal fault and external fault. In other words, when it is internal fault, the component of the flat-wave reactance branch is close to 0; The component of the flat wave reactance branch is much larger than 0 when it is external fault. Simulation results show that HVDC longitudinal protection scheme based on branch current characteristics can quickly and accurately identify fault types in various situations and has a strong ability to withstand transition resistance.